Comparison of the Functional microRNA Expression in Immune Cell Subsets of Neonates and Adults - Yu, Hong-Ren; Hsu, Te-Yao; Huang, Hsin-Chun; Kuo, Ho-Chang; Li, Sung-Chou; Yang, Kuender D.; Hsieh, Kai-Sheng (Frontiers in Immunology, 2016)
Diversity of biological molecules in newborn and adult immune cells contributes to differences in cell function and atopic properties. Micro RNAs (miRNAs) are reported involve in the regulation of immune system. Therefore, determining the miRNA expression profile of leukocyte sub-populations is important for understanding immune system regulation. In order to explore the unique microRNA profiling that contribute to altered immune in neonates, we comprehensively analyzed the functional miRNA signatures of eight leukocyte subsets (polymorphonuclear cells, monocytes, CD4+ T cells, CD8+ T cells, natural killer cells, B cells, plasmacytoid dendritic cells (pDCs), and myeloid dendritic cells (mDCs)) from both neonatal and adult umbilical cord and peripheral blood samples, respectively. We observed distinct miRNA profiles between adult and neonatal blood leukocyte subsets, including unique miRNA signatures for each cell lineage. Leukocyte miRNA signatures were altered after stimulation. Adult peripheral leukocytes had higher let-7b-5p expression levels compared to neonatal cord leukocytes across multiple subsets, irrespective of stimulation. Transfecting neonatal monocytes with a let-7b-5p mimic resulted in a reduction of LPS-induced IL-6 and TNF-alpha production, while transfection of a let-7b-5p inhibitor into adult monocytes enhanced IL-6 and TNF-alpha production. With this functional approach, we provide intact differential microRNA expression profiling of specific immune cell subsets between neonates and adults. These studies serve as a basis to further understand the altered immune response observed in neonates and advance the development of therapeutic strategies.